2020
DOI: 10.1021/acs.analchem.0c03150
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Reactive MALDI Matrix Enabling High-Lateral Resolution Dual Polarity MS Imaging and Lipid C═C Position-Resolved MS2 Imaging

Abstract: Local lipid variations in tissues are readily revealed with mass spectrometry imaging (MSI) methods, and the resulting lipid distributions serve as bioanalytical signatures to reveal cell-or tissue-specific lipids. Comprehensive MSI lipid mapping requires measurements in both ion polarities. Additionally, structural lipid characterization is necessary to link the lipid structure to lipid function. Whereas some structural elements of lipids are readily derived from high-resolution mass spectrometry (MS) and tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 49 publications
(90 reference statements)
1
44
0
Order By: Relevance
“…The resulting oxetanes allow to spatially discern DB position isomers as shown in Fig. 11 [152]. Reactive MALDI-MS 2 I of protonated PC 34:1 from mouse pancreas tissue with 10 μm lateral resolution reveals the presence of two distinct DB position isomers.…”
Section: Mass Spectrometry Imaging and Structure Annotationsmentioning
confidence: 97%
See 2 more Smart Citations
“…The resulting oxetanes allow to spatially discern DB position isomers as shown in Fig. 11 [152]. Reactive MALDI-MS 2 I of protonated PC 34:1 from mouse pancreas tissue with 10 μm lateral resolution reveals the presence of two distinct DB position isomers.…”
Section: Mass Spectrometry Imaging and Structure Annotationsmentioning
confidence: 97%
“…The authors developed a compound that serves as MALDI matrix but also reacts with most neurotransmitters installing a permanent charge and enabling compound identification via MS n . The concept of reactive MALDI matrices for structure diagnostic MSI investigations has further been developed by Heiles and co-workers [151,152]. Instead of reacting compounds with the matrix on-tissue, the authors identified benzophenone-based compounds that function as MALDI matrices but react on-demand, during UV laser irradiation, with DBs of lipids in a PB reaction.…”
Section: Mass Spectrometry Imaging and Structure Annotationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzophenone (BPh) derivatives undergo PB reactions and at the same time show good absorption behavior as needed for the MALDI MS process. This was used by the group of Heiles for the on‐tissue derivatization and detection of unsaturated phospholipids (PLs) [99] and allowed to visualize 12 lipid classes from mouse kidney and pancreas tissue through MALDI MSI [100] …”
Section: Rational Design Of Newly Developed Matrix Systemsmentioning
confidence: 99%
“…Visualization of FA isomers across tissue samples provides critical information to better understand their region-specic functions. It is noted that the Paternò-Büchi reaction, 15,17,36 ozone-induced dissociation (OzID), 16 ozonolysis 37 and m-CPBA epoxidation 29 have been adopted for MS-based mapping of lipid isomers on tissues, however, challenges still remain including low yields, side reactions, and interference from excess on-tissue derivatization reagent. Therefore, the development of novel methodologies for spatial mapping and quantication of FA isomers within biological samples is still in great demand.…”
Section: Introductionmentioning
confidence: 99%